Long-term development of gait after multilevel surgery in children with cerebral palsy: a multicentre cohort study - Dreher, Thomas; Thomason, Pam; Svehlík, Martin; Döderlein, Leonhard; Wolf, Sebastian Immanuel; Putz, Cornelia; Uehlein, Oliver; Chia, Kohleth; Steinwender, Gerhardt; Sangeux, Morgan; Graham, H. K. (Developmental medicine and child neurology, 2018)
Aim We investigated the long-term efficacy and safety of multilevel surgery (MLS) in ambulatory children with bilateral spastic cerebral palsy (CP). Method Two hundred and thirty-one children were evaluated at short term (1.1y, SD 0.4) and long term (9.1y, SD 3.0) follow-up using clinical examination and gait analysis. MLS was investigated by studying changes in the Gait Profile Score (GPS) referenced to the minimally important clinical difference. Results Ambulatory children aged 10 years and 7 months (SD 2y 11mo) at MLS in Gross Motor Function Classification System levels I (19), II (144), and III (68) showed a decrease (improvement) in preoperative GPS from 16.3° (SD 4.8) to 11.3° (SD 3.2) at short-term follow-up, an improvement of 5°. At long-term follow-up, GPS was maintained at 11.4° (SD 3.1). Overall, 177 (76.6%) children maintained their improvement in GPS after 9 years. Interpretation Multilevel surgery is a safe and effective surgical intervention, which leads to a significant improvement in gait kinematics in children with bilateral spastic CP. This study improves our understanding of MLS in the long term and will help to inform families and children when planning for MLS. What this paper adds Largest study of multilevel surgery (MLS) for children with bilateral spastic cerebral palsy, with longest follow-up. MLS resulted in significant long-term improvements in gait function. Minor adverse events were common, while events requiring intervention were uncommon (4% of children). Thirty-nine per cent of children required additional surgery during follow-up. ‘Single-event multilevel surgery’ was changed to the more realistic term ‘multilevel surgery’.
Gesehen am 11.09.2018
Published online 24th November 2017